Relative Age Effect in Junior Padel Players: Insights from National Team Selection at the 2024 Junior European Championships - Rafael Conde-Ripoll; Iván Martín-Miguel; Diego Muñoz; Carlo Ferrara; Bernardino J. Sánchez-Alcaraz; Adrián Escudero-Tena (Applied Sciences)
This study investigated the relative age effect (RAE) in junior padel players participating in the 2024 European Junior Championships by Teams. The sample included 285 athletes (165 boys from 16 boys’ teams and 120 girls from 12 girls’ teams). Dates of birth were categorized into quartiles, and data analysis employed Chi-squared goodness-of-fit tests, Fisher’s exact goodness-of-fit tests, Chi-squared tests, Fisher’s exact tests with Monte Carlo correction (95% CI), and Spearman correlations. The results showed no consistent RAE overall. However, in boys, players born in Q1 (CSR = 2.2) and in the last year of eligibility (CSR = 2.0) were more prevalent in higher-ranked teams. Position directly correlated with quartile (boys: p = 0.015; girls: p = 0.001) and category year (boys: p = 0.032; girls: p = 0.038). These findings suggest that while RAE was not observed across all junior padel players, boys’ teams, particularly in higher ranks, exhibited trends favoring early birth quartiles and the final year of eligibility. Such patterns may influence competitive performance and talent identification. Further research is needed to understand the implications of RAE in youth sports, particularly regarding talent development and team selection processes.